2008
DOI: 10.1007/s11605-007-0275-z
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Laparoscopic Heller Myotomy for Achalasia is Not Influenced by the Degree of Esophageal Dilatation

Abstract: In the past, a Heller myotomy was considered to be ineffective in patients with achalasia and a markedly dilated or sigmoid-shaped esophagus. Esophagectomy was the standard treatment. The aims of this study were (a) to evaluate the results of laparoscopic Heller myotomy and Dor fundoplication in patients with achalasia and various degrees of esophageal dilatation; and (b) to assess the role of endoscopic dilatation in patients with postoperative dysphagia. One hundred and thirteen patients with esophageal acha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 19 publications
4
63
0
1
Order By: Relevance
“…There is a strong association between age at which diagnosis of achalasia is first established and the requirement for HM [50] . For each year of increasing age, the odds ratio for the eventual requirement for myotomy decreases by 0.943 (95% CI: 0.90-0.98).…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong association between age at which diagnosis of achalasia is first established and the requirement for HM [50] . For each year of increasing age, the odds ratio for the eventual requirement for myotomy decreases by 0.943 (95% CI: 0.90-0.98).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, surgical myotomy remains the preferred modality for achalasia in the United States; perhaps because of medical-legal concerns related to PD perforation and the usual more durable response with myotomy [13] . The degree of esophageal dilation of the achalasia esophagus is less of a concern to the surgeon then previously, but the operator must ensure an adequate myotomy and distal esophagectomy (6+ cm), and up to 20% of patients may require repeat intervention [14] .…”
Section: Prior Conventional Treatments For Achalasiamentioning
confidence: 99%
“…Another study showed that patients with stage I-III disease on preoperative evaluation had 90% satisfactory clinical outcome that was maintained during long-term follow-up, whereas patients with stage IV disease responded only 50% of the time and even the responders demonstrated symptom deterioration over time [47]. On the other hand, other studies have shown treatment responses even in (selected) patients with dilated esophageal bodies or sigmoid esophagus [33,104,105]. In addition, the rate of improvement after myotomy even in patients with a normotensive or hypotensive LES has been reported to be similar to those with a hypertensive LES in some other studies [106].…”
Section: Predictors Of Successful Outcomes After Myotomymentioning
confidence: 99%